Primitive neon and helium isotopic compositions of high-MgO basalts from the Kerguelen Archipelago, Indian Ocean - Doucet, Sonia; Moreira, Manuel; Weis, Dominique; Scoates, James S.; Giret, André; Allègre, Claude (Earth and Planetary Science Letters, 2006)
International audience The geochemical characteristics of mildly alkalic basalts (24-25 Ma) erupted in the southeastern Kerguelen Archipelago are considered to represent the best estimate for the composition of the enriched Kerguelen plume end-member. A recent study of picrites and high-MgO basalts from this part of the archipelago highlighted the Pb and Hf isotopic variations and suggested the presence of mantle heterogeneities within the Kerguelen plume itself. We present new helium and neon isotopic compositions for olivines from these picrites and high-MgO basalts (6-17 wt.% MgO) both to constrain the enriched composition of the Kerguelen plume and to determine the origin of isotopic heterogeneities involved in the genesis of Kerguelen plume-related basalts. The olivine phenocrysts have extremely variable 4 He / 3 He compositions between MORB and primitive values observed in OIB (∼90,000 to 40,000; i.e., R / R a ∼8 to 18) and they show primitive neon isotopic ratios (average 21 Ne / 21 Ne ext ∼0.044). The neon isotopic systematics and the 4 He / 3 He ratios that are lower than MORB values for the Kerguelen basalts clearly suggest that the Kerguelen hotspot belongs to the family of primitive hotspots, such as Iceland and Hawaii. The rare gas signature for the Kerguelen samples, intermediate between MORB and solar, is apparently inconsistent with mixing of a primitive component with a MORB-like source, but may result from sampling a heterogeneous part of the mantle with solar 3 He / 22 Ne and with a higher (U, Th) / 3 He ratio compared to typically high R / R a hotspot basalts such as those from Iceland and Hawaii.